2020
DOI: 10.1155/2020/7938149
|View full text |Cite
|
Sign up to set email alerts
|

Toxin Production and Resistance of Staphylococcus Species Isolated from Fermented Artisanal Dairy Products in Benin

Abstract: Staphylococcus species are considered as one of the major pathogens causing outbreaks of food poisoning. The aim of this work was to assess the toxinogenic and antibiotic susceptibility profiles of the strains of Staphylococcus spp isolated from three types of fermented dairy products (yoghourt, millet dêguê, and couscous dêguê). The isolation of the Staphylococcus strains was performed on selective media, and their identification was done using biochemical and molecular methods. The susceptibility at 15 antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…This study employed a purposive sampling design that was carried out to detect the presence of S. aureus strains in dairy farms that have low milking hygiene, which can increase bacterial contamination in cow's milk. 29 In line with this, the research conducted by Khiabanian et al 30 showed that the difference in the number of isolates found could be influenced by differences in study design such as population and geographic distribution of the sample, infection control practices, and the type of antibiotic used, as seen in Figure 3.…”
Section: Discussionmentioning
confidence: 76%
“…This study employed a purposive sampling design that was carried out to detect the presence of S. aureus strains in dairy farms that have low milking hygiene, which can increase bacterial contamination in cow's milk. 29 In line with this, the research conducted by Khiabanian et al 30 showed that the difference in the number of isolates found could be influenced by differences in study design such as population and geographic distribution of the sample, infection control practices, and the type of antibiotic used, as seen in Figure 3.…”
Section: Discussionmentioning
confidence: 76%
“…This study employed a purposive sampling design that was carried out to detect the presence of S. aureus strains in dairy farms that have low milking hygiene, which can increase bacterial contamination in cow's milk. 29 In line with this, the research conducted by Khiabanian et al 30 showed that the difference in the number of isolates found could be influenced by differences in study design such as population and geographic distribution of the sample, infection control practices, and the type of antibiotic used, as seen in Figure 3 mecA PCR results with a positive band at 533 bp. Marker line: 100-bp molecular-weight markers; Line K-: Staphylococcus aureus ATCC 25923 (Negative Control); Line AT28, AT41, and AS109: positive result for mecA gene detection; Line AT21, AT29, AT33, AS67, AS77, AS80, and AS102: negative result for mecA gene.…”
Section: Discussionmentioning
confidence: 76%
“…This study employed a purposive sampling design that was carried out to detect the presence of S. aureus strains in dairy farms that have low milking hygiene, which can increase bacterial contamination in cow’s milk. 32 In line with this, the research conducted by Khiabanian et al 33 showed that the difference in the number of isolates found could be influenced by differences in study design such as population and geographic distribution of the sample, infection control practices, and the type of antibiotic used, as seen in Figure 6 .…”
Section: Discussionmentioning
confidence: 77%